An investigation of characteristics of flow and heat transfer in the two-layer molten pool under swing motion condition. (October 2022) - Zhang, Yapei; Zhan, Dekui; Bai, Jingyuan; Luo, Simin; Li, Yongkang; Tian, Wenxi; Su, G.H.; Qiu, S.Z.; Chen, Peng
Abstract: In-Vessel Retention (IVR) of molten corium is an important strategy for management of severe accidents adopted by some active service generation II plus reactors and advanced generation III reactors like AP1000, Hualong one and APR1400. One of the most important factors contributing to IVR analysis can be attributed to the characteristics of heat transfer in the molten pool in the lower head of reactor pressure vessel (RPV), which directly determines the heat load imposed on the vessel wall of the RPV lower head. Besides, IVR is also an important strategy for management of severe accidents of Ocean Floating Reactor (OFR), whose flow and heat transfer characteristics are influenced by the ocean motion conditions. However, since all previous molten pool experiments were conducted under static condition, characteristics of the heat transfer in the molten pool thus obtained may be different from those under ocean motion conditions, thus not applicable to the latter. To address this issue, in this study, an experimental system was established, which includes a two-layer molten pool test facility and a swing motion platform. Based upon the system, the effects of the swing angle and swing period on the characteristics of heat transfer in the two-layer melt pool were investigated. In addition, a scaling method was proposed to select simulant materials for the two-layer corium pool. Results of the experiment show that the swing period and angle have a significant effect on the temperature field of the molten pool and the rate of heat transfer. We thus suggest that, in future studies, new heat transfer correlations, models and IVR analysis method for ocean floating reactors should be researched and developed to evaluate the IVR design of ocean floating reactors, which is critical for management of severe accidents of the ocean floating reactors. Highlights: Establishing a two-layer melt pool test facility with swing motion condition. Scaling analysis was conducted to select simulant material for two-layer corium pool. Investigating effects of swing angle and period on heat transfer characteristics of melt pool. Temperature stratification in the molten pool decreases with the decrease of the swing period. Peak value of average cooling power ratio increases with the decrease of swing period.